Dickens of London [videorecording (DVD)] - Miller, Marc; Ferguson, Michael; Dotrice, Roy, 1923-2017; Bell, Simon; Foad, Gene (Koch Vision : Manufactured and distributed by KOCH Entertainment, 2007)
Featuring a stellar cast, the 13 part mini-series traces the extraordinary life of Charles Dickens from his penniless childhood in Chatham and London during the 1820s to the unprecedented success he later enjoyed on both sides of the Atlantic.